Congestion and public capital - Walter H. Fisher; Stephen J. Turnovsky (Institute for Advanced Studies (IHS), 1997)
This paper analyzes the impact of public investment on the dynamics of private capital formation in an intertemporal optimizing market-clearing framework. The key feature characterizing the analysis is that the public good is treated as a durable capital good, subject to congestion. We show how in the presence of congestion the effect of government investment on private capital formation involves a tradeoff between the degree of substitution between private and public capital in production and the degree of congestion. Both lump-sum and distortionary tax financing are considered, with this tradeoff being tightened in the latter case.
Keywords: E62; H41; 330; congestion; public capital